The equation [tex]p^3+q^3+r^3=(\frac{1}{p^3}+\frac{1}{q^3}+\frac{1}{r^3})p^2q^2r^2[/tex] has been proved to be true
The equation is given as:
[tex]\frac pq = \frac qr[/tex]
Cross multiply
[tex]pr = q^2[/tex]
Rewrite as:
[tex]q^2 = pr[/tex]
Also, we have:
[tex]p^3+q^3+r^3=(\frac{1}{p^3}+\frac{1}{q^3}+\frac{1}{r^3})p^2q^2r^2[/tex]
Substitute [tex]q^2 = pr[/tex]
[tex]p^3+q^3+r^3=(\frac{1}{p^3}+\frac{1}{q^3}+\frac{1}{r^3})p^3r^3[/tex]
Expand
[tex]p^3+q^3+r^3=\frac{1}{p^3} \times p^3r^3 +\frac{1}{q^3} \times p^3r^3 +\frac{1}{r^3} \times p^3r^3[/tex]
Simplify
[tex]p3+q3+r3=r^3 +\frac{1}{q^3} \times p^3r^3 + p^3[/tex]
Rewrite as:
[tex]p3+q3+r3=r^3 +\frac{1}{q^3} \times (pr)^3 + p^3[/tex]
Substitute [tex]pr = q^2[/tex]
[tex]p3+q3+r3=r^3 +\frac{1}{q^3} \times (q^2)^3 + p^3[/tex]
[tex]p3+q3+r3=r^3 +\frac{1}{q^3} \times q^6 + p^3[/tex]
Divide q^6 by q^3
[tex]p3+q3+r3=r^3 +q^3 + p^3[/tex]
Rewrite the equation as:
[tex]p3+q3+r3=p^3 +q^3 + r^3[/tex]
Hence, the equation has been proved
Read more about equations at:
https://brainly.com/question/13729904